2007
DOI: 10.1007/s00134-007-0561-y
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin reduces vascular hyperpermeability and improves survival in rat septic shock

Abstract: These data suggest that adrenomedullin-related reduction of vascular hyperpermeability might represent a novel and important mechanism contributing to the beneficial effects of this endogenous vasoregulatory peptide in sepsis and septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 43 publications
2
71
1
Order By: Relevance
“…Furthermore, inflammatory conditions such as sepsis or acute lung injury increased adrenomedullin expression [67][68][69], and the inflammatory response and organ damage in mice heterozygous for the adrenomedullin gene were aggravated upon LPS challenge [70]. Treatment with exogenous adrenomedullin improved pulmonary barrier dysfunction caused by different stimuli such as hydrogen peroxide, LPS or Staphylococcus aureus α-toxin and was protective against ventilator-induced lung injury in mice with and without pneumonia [61,[71][72][73][74]. At least two major mechanisms underlie the barrier-protective effect of adrenomedullin: 1) reducing actin-myosin-based endothelial cell contraction [62] and 2) strengthening intercellular adherence junctions [75,76].…”
Section: Improving Pulmonary Barrier Functionmentioning
confidence: 99%
“…Furthermore, inflammatory conditions such as sepsis or acute lung injury increased adrenomedullin expression [67][68][69], and the inflammatory response and organ damage in mice heterozygous for the adrenomedullin gene were aggravated upon LPS challenge [70]. Treatment with exogenous adrenomedullin improved pulmonary barrier dysfunction caused by different stimuli such as hydrogen peroxide, LPS or Staphylococcus aureus α-toxin and was protective against ventilator-induced lung injury in mice with and without pneumonia [61,[71][72][73][74]. At least two major mechanisms underlie the barrier-protective effect of adrenomedullin: 1) reducing actin-myosin-based endothelial cell contraction [62] and 2) strengthening intercellular adherence junctions [75,76].…”
Section: Improving Pulmonary Barrier Functionmentioning
confidence: 99%
“…AM has also been shown to reduce TNF-α expression and release in macrophage cell lines and rat Kupffer cells [33]. More recently, administration of AM to rats with α-toxin-induced sepsis reduced vascular hyperpermeability and resulted in dramatically improved survival rates [31]. Finally, dynamic and robust changes in the expression of AM and its receptors occur in the lungs in response to septic shock [4,22].…”
Section: Introductionmentioning
confidence: 99%
“…1 Adrenomedullin is a peptide produced by multiple tissue types during physiologic stress, and has pluripotent function, including vasodilatory, antimicrobial, and antiinflammatory activity. 2 In animal models of sepsis, [3][4][5] exogenous adrenomedullin reduces acute lung injury, vascular permeability, and death; endogenous overexpression similarly ameliorates the septic insult. Human data are sparse, but early studies 6,7 reported high adrenomedullin levels associated with increased vasodilation and severity of illness in systemic inflammation and septic shock.…”
mentioning
confidence: 99%